HUBUNGAN KECERDASAN INTERPERSONAL DENGAN KOMUNIKASI ANAK USIA 4–5 TAHUN DI PAUD PERMATA HATI ISLAMIC PRESCHOOL TAHUN AJARAN 2016/2017 - Nur Samaratul Qalbi; Muazar Habibi; Baiq Nilawati Astini; I Wayan Karta (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2020)
The purpose of this study was to determine the existence of a positive and significant correlation between interpersonal intelligence and communication for children aged 4-5 years in PAUD Permata Hati Islamic Preschool in the 2016/2017 academic year. The methodology in this research is quantitative associative. There are 2 variables in this study, namely interpersonal intelligence as the independent variable and communication as the dependent variable. The population in this study amounted to 36 children, as well as the number of samples, namely 36 children, because it used a saturated sample, where the number of samples was the same as the total population. The data collection method used is observation. The data analysis technique used is Pearson's product moment formula (simple or single correlation) to calculate the regression between interpersonal intelligence and communication variables. This study has a simple or single correlation test result of 0.918. So, rcount > rtable (0.918 > 0.329). The rtable value was obtained from N = 36 with a significance level of 5%. This shows that there is a positive and significant correlation between interpersonal intelligence and communication for children aged 4-5 years at PAUD Permata Hati Islamic Preschool in the 2016/2017 academic year.